Empowering Students’ Affective Factors in Teaching Speaking through Integrated Communicative Activities - Mujahidah; Faridah Abdul Rauf; Muhammad Zuhri Dj (Asian TESOL Journal, 2022)
This study investigates the students' affective factors in learning to speak through integrated communicative activities. Communicative activities aim to develop students' ability to use language to interact with people in real situations. Practising communicative activities can certainly help students to develop their language abilities. Integrated communicative activities are assumed to be the best way to empower the students' affective factors. Communicative activities are needed to help students to boost the students' anxiety, motivation and self-confidence in learning to speak. The participants were students in the fourth semester of the English Education Department of State Islamic Institute Parepare. The quantitative research was conducted by using a random sampling technique. In-depth analysis showed three results, 1) the students believed they desired to speak in front of the class. They were not afraid and shy when their friend laughed or the teacher correction at them; 2) the students were enthusiastic and spirit about learning as a good opportunity in the future; 3) the students also had confidence that they have intelligence and communication ability. The study's results suggested that integrated communicative activities should be implemented in the class to empower the students' affective factors.